Peningkatan Kualitas Usaha Melalui Pelatihan Manajemen Dan Strategi Pemasaran Pengrajin Sepatu Kulit Desa Tambakrejo Krembung Sidoarjo - Ekantoro, Julyanto; Hanani, Amrozi Wildan; Savitri, Layli (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The purpose of this study is to improve the quality of leather shoe craftsmen's business in Tambakrejo Village, Sidoarjo, by providing useful business management and marketing strategy training. Leather shoe craftsmen in this village face several problems in managing their business, such as limitations in business planning, financial management, and problems in selling their products to more people. In this study, a qualitative method was used, and this training method includes aspects of management and marketing. The focus of business management training is to improve skills in effective production management and human resource management. In contrast, understanding the importance of branding and building local and national market networks is part of the marketing strategy training. The study shows that this training improves the craftsmen's knowledge of the importance of effective management and marketing. Therefore, this study suggests that craftsmen need to get continuous mentoring and improve their digital literacy so that they can optimally utilize technology to promote and develop their businesses.